Inflammasome-mediated mechanisms of systemic inflammation in COVID-19 and asthma - Tatyana I. Vitkina; Tatyana G. Lobova; Tamara T. Bogomaz; Eleonora V. Korableva (Russian Open Medical Journal)
The review examines the formation of inflammasome-mediated mechanisms of systemic inflammation in asthma after COVID-19. It provides insight into the clinical and pathophysiological relationship between asthma and COVID-19. The review summarizes information about the role of the NLRP3 inflammasome in the pathogenesis of asthma and describes in detail its manifestations in various asthma phenotypes. Emphasizing the significance of the inflammatory-mediated immune response during coronavirus infection in patients with bronchopulmonary pathology, the review outlines the consequences of hyperactivation of the NLRP3 pathway, leading to increased production of cytokines, the appearance of neutrophil and monocyte-derived traps, induction of pyroptosis and the development of complications.